Pengaruh Income Smoothing dan Corporate Sosial Responsibility terhadap Nilai Perusahaan - Anggun Anggraini; Indawati Indawati; Yefita Lahagu; Holiawati Holiawati; Endang Ruhiyat (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2023)
This study aims to test and analyze the effect of Income Smoothing and Corporate Social Responsibility on Company Value. This type of research is quantitative research, using secondary data. The data analysis method used is a panel data regression test using Microsoft Excel and Eviews 9 applications. The population in this study is all food and beverage companies listed on the Indonesia Stock Exchange in the period 2017 to 2021. The data collection technique in this study is a purposive sampling technique with the results of 72 study populations into 22 research samples processed in this study. The results showed that Income Smoothing and Corporate Social Responsibility simultaneously affect the Value of the Companyn. While partially, Income Smoothing has no effect on Company Value and Corporate Social Responsibility has no effect on Company Value.